Accessing medical records for research in South African public hospitals: a reflective narrative - Daphney Nozizwe Conco; Boitumelo Komane; Emelda Boikanyo; Zinhle Khadija Maneli; Mothupi Boikanyo; Sharon Fonn (BMC Health Services Research)
Abstract Background Access to medical data is important for health system research in South Africa. Researchers must obtain authorization from gatekeepers to enter hospitals and access medical records. They engage with street-level bureaucrats to retrieve specific records and extract necessary data. This paper reflects on our experiences accessing patient records in a nationally representative sample of 60 public hospitals in South Africa. Methods We chose narrative inquiry to deeply explore researchers' experiences accessing medical records in South African public hospitals. This qualitative method focuses on individuals' stories and personal experiences, providing rich, detailed insights into complex, context-dependent phenomena. Field reports documented our reflections and experiences during each hospital visit. Additionally, we conducted debriefing sessions to further explore these experiences. The themes that emerged from the field reports and debriefing sessions prompted us to delve deeper into the research process. To explore these themes, we conducted a focus group discussion (FGD) with all researchers. The FGD transcript and field reports were analyzed using MAXQDA. We adopted Gibbs's reflective model, incorporating structured debriefing steps, to present our findings. Results Our reflections highlight the challenges encountered during the ethical review process, engagements with numerous gatekeepers, and street-level bureaucracy. The ethics review process experienced significant delays. Obtaining permission from various gatekeepers was arduous and complex, often presenting logistical challenges. We had both positive and negative experiences with the street-level bureaucrats, including hospital staff responsible for creating, curating, and safeguarding medical records. Some exhibited resistance that appeared to stem from their frustrations with superiors. Public hospital records were mostly poorly curated. Conclusion Ethical review is essential for guiding complex research like access to abortion. However, an overcautious approach might impede needed research with vulnerable populations. Researchers need to be up to date with local processes and have sufficient resources to gain gatekeepers’ permission to access public hospitals. Understanding street-level bureaucracy is imperative for researchers who need to interact with various hospital personnel to access medical records. The state of record-keeping in South African public hospitals may reflect the overall state of the health system, including examples of excellence and mediocrity.